2000
DOI: 10.1902/annals.2000.5.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Variables Affecting Survival of Single‐Tooth Hydroxyapatite‐Coated Implants in Anterior Maxillae at 3 Years

Abstract: Three-year post-placement survival data suggest that the use of HA-coated, grooved, endosseous implants to support maxillary anterior single-tooth replacements is a predictable and reliable procedure that can offer significant benefits. Longer implants demonstrated higher survival than shorter implants. The use of preoperative antibiotics was nearly significant to implant survival, and there was an increase in mean PTVs observed over the duration of the study. Further research is needed to assess stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The initial screening of titles and abstracts resulted in 28 full‐text papers; 13 were cited in more than one research of terms. The full‐text reports of the remaining 15 articles led to the exclusion of 4 because they did not meet the inclusion criteria: two articles did not inform of the number of failed implants in each group, one article did not clearly inform of the number of implants in each group, and one article did not evaluate implant failures. Orenstein et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial screening of titles and abstracts resulted in 28 full‐text papers; 13 were cited in more than one research of terms. The full‐text reports of the remaining 15 articles led to the exclusion of 4 because they did not meet the inclusion criteria: two articles did not inform of the number of failed implants in each group, one article did not clearly inform of the number of implants in each group, and one article did not evaluate implant failures. Orenstein et al .…”
Section: Resultsmentioning
confidence: 99%
“…Orenstein et al . informed of the number of implants placed and the number of failed implants in patients taking pre‐ and post‐operative antibiotics separately. However, it was not informed whether, for example, some patients who did not take antibiotics pre‐operatively made use of antibiotics post‐operatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Block and Kent 2 reported a cumulative success rate of 9‐.1% over a 3‐ to 4‐year period for HA‐coated cylindrical implants. Orenstein et al 3 reported that the establishment and maintenance of osseointegration was 97.3% at 3 years in single‐tooth HA‐coated implants in the anterior maxilla. In a clinical study of 388 implants with a mean follow‐up of 60 months, Schwartz‐Arad et al 4 found that the marginal bone loss was significantly lower in commercially pure (cp) titanium implants, whereas HA‐coated implants had a significantly higher 12‐year survival rate than cp titanium implants (93.2% versus 89%).…”
mentioning
confidence: 99%
“…All patients were aware of the study method and after being informed of the potential problems and risks, they signed an informed consent form. Patients were selected based on the following criteria: Inclusion criteria: The presence of a hopeless tooth in the anterior or premolar region, the presence of an adequate mesiodistal space (6.5 mm or more) for placement of an implant with 3.5-mm or maximum possible diameter based on the anatomy of the area, the presence of a bundle of keratinized mucosa around the hopeless tooth, the presence of adjacent teeth, either intact or restored using a proper and functional restoration with no pathological periradicular lesions, proper oral hygiene (plaque index below 20%), and normal occlusion [5,[10][11][12].…”
Section: Methodsmentioning
confidence: 99%